Highly active halogen bonding and chalcogen bonding chloride transporters with non-protonophoric activity - Bickerton, L; Docker, A; Sterling, A; Kuhn, H; Duarte, F; Beer, PD; Langton, M (Wiley, 2021)
Synthetic anion transporters show much promise as potential anti-cancer agents and therapeutics for diseases associated with mis-regulation of protein anion channels. In such applications high activity and anion selectivity are crucial to overcome competing proton or hydroxide transport which dissipates cellular pH gradients. Here we report highly active bidentate halogen bonding and chalcogen bonding anion carriers based on electron deficient iodoand telluromethyl-triazole derivatives. Anion transport experiments in lipid bilayer vesicles reveal record nanomolar chloride transport activity for the bidentate halogen bonding anion carrier, and remarkably high chloride over proton/hydroxide selectivity for the chalcogen bonding anionophore. Computational studies provide further insight into the role of sigma-hole mediated anion recognition and desolvation at the membrane interface. Comparison with hydrogen bonding analogues demonstrates the importance of employing sigma-hole donor motifs in synthetic anionophores for achieving both high transport activity and selectivity.